Linoleic Acid Inhibits the Release of Leishmania donovani Derived Microvesicles and Decreases Its Survival in Macrophages - Saini, Sheetal; Rai, Ambak Kumar (Frontiers in Cellular and Infection Microbiology, 2020)
Visceral leishmaniasis is a neglected tropical disease caused by Leishmania (L.) donovani parasite in the Indian subcontinent. Macrophages (mφ) are the harboring cells for parasite and their interactions dictate the pathogenesis of this disease. Polyunsaturated fatty acids are an integral part of the mφ cell membrane and are derived from linoleic acid (LA), which is a principal essential fatty acid. Here, we have investigated the effect of the simultaneous presence of LA during L. donovani infection in mφ. Treatment with LA suppresses the parasitic load in mφ (kDNA expression) and promotes the Th-1 type immune response (IL-12, iNOS). However, no significant change in kDNA expressions was observed when L. donovani promastigotes were treated with LA. Intrigued by this observation, we explored mechanism(s) by which LA promoted the protective type immune response in infected mφ. Interestingly, LA decreased the release of L. donovani derived extracellular vesicle later characterized as microvesicles. Moreover, these microvesicles were suppressive concerning their bias toward the Th-2 type of immune responses (IL-10, Arginase) in mφ. We suggest that LA plays a protective role in the immune response against L. donovani infection by inhibiting the release to Leishmania derived microvesicles and thus promoting Th-1 type immune response in mφ.